Воздействие экспериментального гипокинетического стресса на простатические регионы и сосуды микроциркуляторного русла предстательной железы крыс - Лугин, И.А.; Троценко, Б.В. (Таврический медико-биологический вестник, 2013)
Морфологічними і ультраструктурнимі методами вивчено вплив гіпокинетіческого стресу на стан простатичних регіонів передміхурової залози щурів. В результаті дослідження встановлено, що ключову роль у процесах морфологічних змін в епітелії простати і ендотелії гемокапілярів при експериментальному гіпокінетичному стресі відіграють процеси дисциркуляторних порушень в судинах мікроциркуляторного русла передміхурової залози. Встановлено, що гіпокінетичний стрес різної тривалості на ультраструктурному рівні в клітинах ендотелію гемокапілярів передміхурової залози на 9 добу впливу у щурів всіх вікових груп призводить до проявів адаптивно-компенсаторних реакцій, а на 14 добу експерименту виникають прояви дисфункції ендотелію, виражені в інтрацелюлярному набряці, паранекрозі і некрозі ендотеліоцитів гемокапілярів. Based on a morphological and ultrastructural examination, were investigated the effect of hypokinetic stress in to prostatic regions and capillaries networks. As a result of experimental researches we found that the key role in morphological changes in prostatic epithelium and endothelium of hemocapillaries due to the effect of hypokinetic stress resulted in the discirculatory disorders in capillary networks. We also found, that hypokinetic stress during the 9 days immobilization influenced rats of all age groups by formation of figures of adaptive-compensatory reactions in tissues and endothelium of the prostate gland, as a result of stromal-epithelial interactions. But for 14 days action of hypokinetic stress, it initiated the endothelium’s dysfunction, which is expressed in intracellular edema, the phenomenon of paranecrosis and necrosis in endothelial cells of blood capillaries, and the disintegration of connective tissue in stroma of prostate gland.